Mitigating T-2 toxin toxicity in Quail: The protective power of sodium butyrate - Huanni Song; Xueyan Zhu; Weiping Hua; Yihao He; Yang Liu; Changyu Cao (Poultry Science)
As one of the most common worldwide contaminants in agricultural production, the T-2 mycotoxin is commonly found in moldy feed and its raw materials. It can slow the growth and suppress the immune function of farm animals, resulting in reduced economic benefits. As a feed additive, sodium butyrate can enhance immune function. However, the toxicological effects of the T-2 toxin on the spleen, thymus, and bursa of Fabricius and the protective mechanism of sodium butyrate against the T-2 toxin in quails are not known. In this study, 1-day-old Korean quails were fed either with T-2 toxin (0.9 mg/kg) spiked food or with spiked food and sodium butyrate (500 mg/kg) as an antagonist, to construct an experimental animal model. Histopathological changes in the immune organs (spleen, thymus, and bursa of Fabricius) of the quails under sub-chronic toxicity of T-2 toxin were observed after 28 days of continuous treatment. The effects of the T-2 toxin and sodium butyrate on the fibrosis of the immune organs were investigated by MASSON staining and fibrosis gene expression, while the effects of the T-2 toxin and sodium butyrate on apoptosis of the immune organs were investigated by TUNEL assay. The expression of apoptosis-related genes was also measured to evaluate the effects of the T-2 toxin on pathological damage, fibrosis, apoptosis, and CYP450 homeostasis while the antagonistic effect of sodium butyrate on the quail immune organs was also measured. Results showed that sodium butyrate could effectively alleviate pathological damage, fibrosis, apoptosis, abnormal activation of the heterologous nuclear receptor pathway, and the disruption of CYP450 homeostasis induced by the T-2 toxin in quail immune organs.